Uplifting leadership for real school improvement—The North Coast Initiative for School Improvement: An Australian telling of a Canadian story - Chaseling, Marilyn; Boyd, William Edgar; Smith, Robert; Boyd, Wendy; Shipway, Bradley; Markopoulos, Christos; Foster, Alan; Lembke, Cathy (Alberta Journal of Educational Research, 2017)
This paper reports on a preliminary Australian adoption and adaptation, in the North Coast region of New South Wales, Australia, of the Townsend and Adams’ model of leadership growth for school improvement in Alberta. The Australian adaptation of this Alberta model has been named the North Coast Initiative for School Improvement (NCISI). The participants comprise nine university academics and almost one hundred regional school leaders. Leadership is developed through continuing and regular collaborative-inquiry and generative-dialogue meetings between the academics and school leaders. The aim is to improve school leadership with the primary purpose of improving student outcomes. Provisional evaluation records significant positive changes in school leadership across the region. Convergence and divergence of the Australian and Canadian models are explored. The Australian adaptation requires some modification to suit local education processes and context. In particular, there has been the development of some divergence in approaches, especially in working in individual schools or clusters of schools. While the program has only been running for a comparatively short time, and therefore formal program evaluation is only commencing, preliminary evidence suggests significant traction and success in the Australian context. The paper concludes with some tentative implications for the future development of this model in the Australian context: how can the model be conceptualised and delivered to a wider audience in the years ahead. Cet article porte sur l’adoption et l’adaptation préliminaire du modèle de Townsend et Adam sur le développement du leadership pour l’amélioration des écoles en Alberta. Ce modèle albertain a été mis en œuvre dans la région de la côte nord de la Nouvelle-Galles du Sud en Australie et nommé North Coast Initiative for School Improvement (NCISI). Les participants comptent neuf universitaires et presque cent dirigeants d’écoles régionales. Des réunions continues et régulières, reposant sur la recherche collaborative et le dialogue génératif, ont lieu entre les universitaires et les dirigeants d’école pour avancer le développement du leadership. L’objectif d’améliorer le leadership scolaire vise principalement le rehaussement du rendement des élèves. Les résultats provisoires de l’évaluation révèlent des changements positifs significatifs dans la direction des écoles de toute la région. Nous explorons les points de convergence et de divergence des modèles australien et canadien. L’adaptation australienne nécessite certaines modifications de sorte à convenir aux procédés et au contexte éducatif locaux. Plus particulièrement, une certaine divergence s’est développée dans les approches, notamment quant au travail dans les écoles particulières ou dans les groupements d’écoles. Le programme étant en œuvre depuis une période relativement courte, l’évaluation formelle en est à ses débuts, mais les résultats préliminaires portent à croire qu’il gagne du terrain et connait un succès dans le contexte australien. L’article conclut en présentant des retombées préliminaires pour le développement à l’avenir de ce modèle en Australie, notamment par rapport à sa conceptualisation et sa prestation à un plus grand public.